2013
DOI: 10.1111/gfs.12081
|View full text |Cite
|
Sign up to set email alerts
|

The variation in morphology of perennial ryegrass cultivars throughout the grazing season and effects on organic matter digestibility

Abstract: 63The grass plant is comprised of leaf, pseudostem, true stem (including inflorescence) 64 and dead. These components differ in digestibility and variations in their relative 65 proportions can impact sward quality. The objective of this study was to determine the 66 change in the proportion and organic matter digestibility (OMD) of leaf, pseudostem, 67 true stem and dead components of four perennial ryegrass cultivars (two tetraploids: 68

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 35 publications
5
45
1
3
Order By: Relevance
“…The high dose of inulin (PR300) x rumen degradable protein interactions may have suppressed digestibility by affecting the fermentation parameters in the fermenter. Beecher et al (2013) stated that the highest and lowest organic matter digestibilities of various PR cultivars were 75.2 and 69.6%, respectively. The findings of the present study for organic matter digestibility in all groups were similar to those of Beecher et al (2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high dose of inulin (PR300) x rumen degradable protein interactions may have suppressed digestibility by affecting the fermentation parameters in the fermenter. Beecher et al (2013) stated that the highest and lowest organic matter digestibilities of various PR cultivars were 75.2 and 69.6%, respectively. The findings of the present study for organic matter digestibility in all groups were similar to those of Beecher et al (2013).…”
Section: Resultsmentioning
confidence: 99%
“…Beecher et al (2013) stated that the highest and lowest organic matter digestibilities of various PR cultivars were 75.2 and 69.6%, respectively. The findings of the present study for organic matter digestibility in all groups were similar to those of Beecher et al (2013). Jensen et al (2003) reported that IVTD DM and IVTD NDF values for perennial ryegrass were higher than those obtained in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of sampling date on grass composition was not unexpected, given the normal changes that take place in grass quality over the season (Beecher et al ., ). Herbage quality was high, however, and the composition similar to that offered in a number of recent grazing studies (Vance et al ., ; Jiao et al ., ; Purcell et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Los raigrás tetraploides presentan un mayor requerimiento de nutrientes, debido a la mayor síntesis de forrajes y valor nutricional respecto a los diploides (Beecher et al, 2013). Sin embargo, cuando se presentan limitaciones en la disponibilidad de nutrientes edáficos y ambientales, los raigrás diploides pueden presentar una mayor respuesta productiva respecto a los tetraploides (Posada et al, 2013).…”
Section: Periodo De Producción De Gramíneas Y Leguminosasunclassified